A busca pela consensualidade da Administração Pública: gestão de conflitos e desjudicialização da saúde - Parahyba, Caroline de Paula Cavalcante (2023)
The phenomenon of the judicialization of health demonstrates, on the one hand, the legitimate demand of citizens to guarantee the right to health protected by the Federal Constitution of 1988, on the other hand, it reveals the structural problems and deficiencies in the provision of health services by the Unified Health System (SUS) to ensure this right, as well as exposes the limitations of the Judiciary to resolve health conflicts, which involve public health policies. The high number of lawsuits and the consequent slowness of the Judiciary Power influenced the search for ways to de-judicialize, culminating in the appreciation of the application of consensual instruments of conflict resolution, which expands the conceptual dimension of access to justice, in the sense that this it is not only related to jurisdiction, but includes the multiple “doors” of dispute solutions, and the most appropriate means must be chosen for each type of conflict. In this sense, with the aim of solving the problem of the judicialization of health, it is observed that the National Council of Justice (CNJ) adopted some strategies to bring the judicial system closer to the health system. Likewise, in some regions of the country, the institutionalization of extrajudicial adoption of resolutions of conflicts in health is also verified. However, despite the commendable contribution of the adoption of consensual means of resolving conflicts in health, applied in a judicial and extrajudicial way, by the Judiciary and institutional actors, it is clear that such conflict management instruments for the dejudicialization of health remains outside the Unified Health System (SUS). Given this, the question arises whether conflict management can be used for public health policy. Thus, the present research was carried out through an inductive methodological approach, based on a bibliographical review, and its general objective is to seek to achieve conflict management strategies that can be applied within the scope of the Health Secretariats, in all its levels, to contain the judicialization of health. Specifically, the objective is to study the fundamental right to health and the consequences of its judicialization, in addition to analyzing the possibility for the Public Administration to adopt consensual means of resolving conflicts in the field of public health. As a result, it was found that conflict management, in particular health mediation, can be applied within the scope of the Health Secretariats, at all levels, to de-judicialize health, and, with that, contribute to the public policy of health, since it generates savings in relation to the public budget allocated to the SUS, concentrates expenses for the real implementation of public health policies and, mainly, seeks to improve the service of users of the Brazilian health system, including their greater participation in taking of decisions.